CMHSU: An R Statistical Software Package to Detect Mental Health Status, Substance Use Status, and Their Concurrent Status in the North American Healthcare Administrative Databases - Mohsen Soltanifar; Chel Hee Lee (Psychiatry International)
The concept of concurrent mental health and substance use (MHSU) status and its detection in patients has garnered growing interest among psychiatrists and healthcare policymakers over the past four decades. Researchers have proposed various diagnostic methods, including the Data-Driven Diagnostic Method (DDDM), for the identification of MHSU. However, the absence of a standalone statistical software package to facilitate DDDM for large healthcare administrative databases has remained a significant gap. This paper introduces the R statistical software package CMHSU (version 0.0.6.9), available on the Comprehensive R Archive Network (CRAN), for the diagnosis of mental health (MH) status, substance use (SU) status, and their concurrent (MHSU) status. The package implements DDDM using hospital and medical service physician visit counts along with maximum time span parameters for MH, SU, and MHSU diagnoses. A simulated real-world dataset incorporating fentanyl is presented to examine various analytical aspects, including three key dimensions of MHSU detection based on the DDDM framework, as well as temporal analysis to demonstrate the package’s application for healthcare policymakers. Additionally, the limitations of the CMHSU package and potential directions for its future extension are discussed.